ASPEK SOSIAL DAN NILAI DALAM PARIBASA BALI JENIS SLOKA SEBAGAI KEARIFAN LOKAL MASYARAKAT BALI - Apriani, Ni Wayan (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2025)
Bali travel agencyis one form of Balinese culture that contains noble values ​​and has a great influence on the lives of Balinese people. Sloka is one type of Balinese paribasa classified by I Nengah Tinggen in his book entitled Aneka Rupa Paribasa Bali. In Bali, Sloka is known as one of the Balinese paribasa which is a figure of speech, which compares something with the state of objects, animals, and other characteristics in order to provide advice, deny, debate, and give advice to the listener in a subtle, precise, and precise way so that it will cause the listener to start the process of thinking about the intent or meaning of the sloka uttered by the speaker. The theories used in this study are value theory and sociology of literature theory. The type of research used is qualitative research. The data collection method used is document recording with processing techniques using non-statistical analysis techniques with induction and argumentation techniques. The results of this study are: 1). The social aspects contained in Balinese paribasa, especially sloka are cultural aspects and language aspects. The cultural aspect is seen from the daily life of Balinese people in their social interactions. While the language aspect is seen from the use of kepara or everyday language as the Balinese language of instruction. 2). The values ​​contained in several Balinese paribasa, especially sloka in this study are religious values, logical values, ethical values, and also aesthetic values.